2016
DOI: 10.1039/c6tc02656g
|View full text |Cite
|
Sign up to set email alerts
|

Conformal oxide nanocoatings on electrodeposited 3D porous Ni films by atomic layer deposition

Abstract: A versatile chemical synthesis procedure to obtain Al2O3 and Co2FeO4 nanolayers conformally coating a three-dimensional (3D) porous Ni film is presented. First, porous Ni is grown by hydrogen bubble template-assisted electrodeposition. Subsequently, Al2O3 and Co2FeO4 layers, with thickness ranging from 5 nm to 25 nm, are directly deposited onto the pore walls by atomic layer deposition, while maintaining the porous architecture and magnetic properties of the Ni scaffold. The crystal structure, thickness and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…30−32 In fact, we proposed the combination of ED and ALD to prepare composite layers consisting of 3D macroporous magnetic metals coated with metal oxide nanolayers, i.e., Ni/Al 2 O 3 and Ni/Co 2 FeO 4 . 33 It was demonstrated that both the porosity and the magnetic properties of the electrodeposited metallic matrix were maintained after the ALD step under optimized ALD conditions. However, the ALD deposition was only tested on metallic films exhibiting large pore sizes, on the order of 5−15 μm.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…30−32 In fact, we proposed the combination of ED and ALD to prepare composite layers consisting of 3D macroporous magnetic metals coated with metal oxide nanolayers, i.e., Ni/Al 2 O 3 and Ni/Co 2 FeO 4 . 33 It was demonstrated that both the porosity and the magnetic properties of the electrodeposited metallic matrix were maintained after the ALD step under optimized ALD conditions. However, the ALD deposition was only tested on metallic films exhibiting large pore sizes, on the order of 5−15 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic layer deposition (ALD) turns out to be a powerful deposition technique that allows not only precise control over the composition of the deposited materials, but also these can continuously coat high aspect-ratio substrates [30][31][32] . In fact, we proposed the combination of ED and ALD to prepare composite layers consisting of 3D macroporous magnetic metals coated with metal oxide nanolayers, i.e., Ni/Al2O3, Ni/Co2FeO4 33 . It was demonstrated that both the porosity and the magnetic properties of the electrodeposited metallic matrix were maintained after the ALD step under optimized ALD conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From electrochemical data presented in Table 3, electrocatalytic behavior could be enhanced by decreasing pore size. So that, According to Abdel-Karim and Halim [10,11], the βc for different nickel-based alloys was in range from 50 to 190. So that micro porous Ni deposits have a high catalytic value as it compares with other works.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…Porous structures, with much larger surface area-to-ratio compared to their fully dense counterparts, are very appealing to enhance certain physical-chemical properties. Nanostructured porous materials have received considerable attention in areas like batteries [11], electrocatalysis [12], super-capacitors [13], or magnetic micro/nanoelectromechanical systems.…”
Section: Introductionmentioning
confidence: 99%